DIAGNOSTIC ACCURACY OF MODIFIED EARLY OBSTETRIC WARNING SYSTEM FOR PREDICTION OF MATERNAL MORBIDITY - Zohra, Sadaf; Urooj, Uzma; Khalid, Nayla; Khan, Sumaira; Siraj, Asifa; Rana, Munawar Jannat (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the diagnostic accuracy of modified early obstetric warning system for predicting maternal morbidity keeping ICU admission as “gold standard”.Study Design: Cross sectional validation study.Place and Duration of Study: Department of Obstetrics and Gynecology, Pak Emirates Military Hospital, Rawalpindi, from Oct 2018 to Apr 2019.Methodology: A total of 205 patients of singleton pregnancy, post-natal period